Phases in the Lifecycle of a Company and the Profitability of Industrial Companies - Kuś Agnieszka; Żurakowska-Sawa Joanna (Studia Ekonomiczne i Regionalne, 2017)
Subject and purpose of work: The aim of this study is to analyse the profitability level of industrial companies in various phases of their lifecycle. Materials and methods: The article uses data from individual annual financial statements of industrial companies in accordance with the classification of the Warsaw Stock Exchange. In order to investigate whether there are essential differences in the level of profitability of companies in various phases of their lifecycle, due to significant deviations from normality, the nonparametric Kruskal-Wallis H test was used. To find out which lifecycle phases differ significantly in terms of the level of analysed profitability ratios, a test of multiple comparisons of medium ranks was used (Post-hoc Dunn’s test). Results: The obtained research results show that a given lifecycle phase significantly differentiates the level of the analysed profitability indices. Conclusions: Based on the conducted research, it was found that the company’s lifecycle phase statistically significantly differentiates the level of the analysed profitability indices. In the early phases of the lifecycle, the level of profitability in the surveyed companies increased gradually reaching maximum and stable values in the phase of maturity or shake-out, after which it decreased in the decline phase. This points to an evolutionary transition of individual companies to the next phase of the lifecycle.